Հինայադրման արարողության խորհուրդը հայոց հարսանեկան ծիսակարգում - Նարինե Շամամյան (Հայկական ՍՍՀ գիտությունների ակադեմիա)
В армянском свадебном цикле день наложения хны четко определен. Во всех этнопровинциях этот день приходится на ночь пятницы, но иногда бывают исключения. Весь процесс наложения хны сопровождается торжественными зрелищами, неотделимой частью которых являются сольные пляски, песни и шествия. Церемония проводилась в первую очередь в доме жениха, а затем дома у невесты. Henna ceremony day is clearly fixed within Armenian wedding cycle. In all Armenian ethnoprovinces this ritual is organized on Friday night; but sometimes there can be exceptions. The whole process of Henna ceremony is accompanied by ceremonial performances, which include sacral dances and songs. First of all, the ceremony is held in bridegroom’s house and after in bride’s house.
Keywords: History; Ethnography; G Geography; Anthropology; Recreation; GT Manners and customs